Electrical Characterization of Strain Effects on Bacterial Nanocellulose Treated with Carbon Nanoparticles - Farjana, Sadia (My University, 2012)
Nanocellulose, having attractive properties such as flexibility, biocompatibility, light weight, low cost and recycling possibilities, is a suitable material for sensors and actuators. Strain sensitive flexible, electrically conductive nanostructured bacterial nanocellulose (BNC) samples were obtained by modification with carbon nanoparticles. Different types of modifying agents such as double walled carbon nanotubes (DWCNT), multiwalled carbon nanotubes (MWCNT) and graphitized carbon nanoparticles (GNP) have been used to make the nanocellulose conductive. The electrical conductivity depends on the modifying agent and its dispersion process. In this project the strain effects on the mechanical and electrical properties of treated BNC samples have been investigated. To observe the strain induced electromechanical response a constant tensile force has been applied to the sample. The samples have piezoresistive properties. There is a correlation between the conductivity and the sensitivity of the samples. Keywords: strain sensor, nanocellulose, bacterial nanocellulose, carbon nanotubes, conductivity.
Keywords: Nanoteknik; Materialvetenskap; Nanovetenskap och nanoteknik; Nano Technology; Materials Science; Nanoscience & Nanotechnology